Evaluation of promoting industrial symbiosis in a chemical industrial park: A case of Midong - Guo, Bin; Geng, Yong; Sterr, Thomas (Journal of cleaner production, 2016)
Circular economy (CE) is key national strategy of China to achieve its long-term sustainable development. Industrial symbiosis (IS) is one practical approach to promote CE for achieving both environmental and economic benefits simultaneously. Chemical industry has a feature of various material and energy flows and is regarded as one key industry to promote IS. However, quantitative analysis of economic and environmental consequence for IS activities is still rare, especially for chemical industrial parks in western China. Under such a circumstance, this study is aiming to shed light on the current IS activities in a typical chemical industrial park in western China, so as to quantitatively evaluate the environmental benefits and economic benefits of IS, including the benefits of each IS chain, the benefits of each participated industrial company and the total benefits of the whole IS network in Midong Chemical Industrial Park (MCIP). Results show that: the annual exchanged volume of undesired material from 32 IS activities in MCIP was more than 4.74 million tons per year, covering 19 different kinds of undesired materials and involving 18 industrial companies within MCIP. The top four exchanged materials were carbide slag, coal gangue, fly ashes and slag, with the exchanged volumes of 1.07, 0.97, 0.92 and 0.68 million tons per year, respectively. From the perspective of IS chains, IS chain number 1 (carbide slag exchange between Huatai Chemical Corp. and Tianshan Cement Corp.) gained the most environmental benefits, with more than 2 million tons and the most economic benefit of 154 million RMB (25.08 million US dollar) per year. From the perspective of industrial companies, Huatai Chemical Corp. received the most economic benefits, while Shenhua Thermal Power Plant and Tianshan Cement Corp. received the most environmental benefits. Totally, IS activities contributed 5.86 million tons of environmental benefits and 382.43 million RMB (62.29 million US dollar) of economic benefits to MCIP. In order to further promote IS in MCIP, several recommendations were proposed, such as increasing CE awareness and environmental awareness of all the stakeholders, restriction of virgin resources, encouragement of urban symbiosis, establishment of a functional information platform and improvement of CE-related technologies.